Waqf Dispute Resolution: A Juridical Review of Alternative Dispute Resolution Mechanisms - Sri Azriani; Raihan Qodrian (ISNU Sumatera Utara, 2025)
This case study examines alternative dispute resolution related to waqf, a charitable practice that has significance in Islamic and social law. Waqf disputes often occur due to differences in interpretation of waqf agreements, non-transparent management of waqf assets, or changes in economic and social conditions. The settlement of waqf disputes requires an approach that is in accordance with the principles of Islamic law, as well as effective and fair in safeguarding the interests of all parties. This study uses a normative juridical method with a case study approach to examine the applicable legal provisions and their application in the practice of resolving waqf disputes. The results of the study show that alternative methods such as mediation and deliberation are preferred over litigation in resolving waqf disputes. This process is considered faster, cost-effective, and able to create a more peaceful settlement in accordance with Islamic values. In conclusion, alternative dispute resolution, especially mediation, offers a more responsive and harmonious mechanism in resolving waqf disputes. Therefore, it is recommended to strengthen the role of faith-based mediation institutions and raise awareness of the importance of peaceful dispute resolution in the context of waqf, in order to ensure sustainable and equitable waqf management.